2018
DOI: 10.1159/000488441
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Diagnosis of Neoplastic or Malignant Hürthle Cell Lesions: A Chimera?

Abstract: Objective: We aimed to review all cytological specimens with Hürthle cells (HC) diagnosed in our institution, identify cytological features related to neoplastic (adenoma or carcinoma) and malignant histology, and discuss the role of clinicopathological findings and clinical management in these cases. Study Design: We included 359 thyroid fine-needle aspiration cytology cases in our study. We reviewed the clinical and cytological features of surgical cases and correlated them with histological diagnosis. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…In an elegant study, constructed in a similar fashion to ours but only evaluated cytologic features, Elliott et al reported that the combination of absent colloid, absent chronic inflammation, non‐macrofollicular architecture (single isolated cells, microfollicles, or 3‐D groups), and TBV correctly identified HC neoplasms in 86% of their cases 16 . Some authors reported that anisonucleosis, hypercellularity, and absent colloid, among other features, were associated with neoplasia and malignancy 15–21,23,26 . Our data corroborated some of the above‐listed criteria, but did not support other criteria previously cited to be diagnostic of neoplasia or malignancy.…”
Section: Discussioncontrasting
confidence: 59%
“…In an elegant study, constructed in a similar fashion to ours but only evaluated cytologic features, Elliott et al reported that the combination of absent colloid, absent chronic inflammation, non‐macrofollicular architecture (single isolated cells, microfollicles, or 3‐D groups), and TBV correctly identified HC neoplasms in 86% of their cases 16 . Some authors reported that anisonucleosis, hypercellularity, and absent colloid, among other features, were associated with neoplasia and malignancy 15–21,23,26 . Our data corroborated some of the above‐listed criteria, but did not support other criteria previously cited to be diagnostic of neoplasia or malignancy.…”
Section: Discussioncontrasting
confidence: 59%
“…The cytological criteria for Hürthle cell neoplasm included the absence or scarcity of colloid and the absence of lymphoplasmacytic infiltration, along with the presence of hypercellularity and the exclusivity of oncocytes, small cell dysplasia, large cell dysplasia, dyscohesive single cell pattern, crowded syncytial arrangements and, in some cases, transgressing vessels. Unfortunately, there are no unequivocal criteria for distinguishing HTC from HTA [4]. The FNA outcome in these cases is equivocal and it is usually classified into the category IV: suspicion of follicular neoplasm (SFN), suspicion of Hürthle cell tumor (SHCT) or the category III: follicular lesion of undetermined significance (FLUS)/atypia of undetermined significance (AUS) of the Bethesda System for Reporting Thyroid Cytopathology (BSRTC) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostically determining the appropriate category is a complex process which involves more than just evaluating cytomorphological features and statistics. It must be emphasised that analysing variables singly or in pairs is less informative than evaluating a group of variables according to specific patterns, as suggested in other studies . For instance, the combination of microfollicular pattern, nuclear crowding and transgressing vessels may discriminate between follicular neoplasm and hyperplasia (see Results section).…”
Section: Discussionmentioning
confidence: 61%